AN EMPIRICAL ANALYSIS ON INTELLIGENT IOT DEVICE FOR THE ASSESSMENT OF SHORT-TERM CARDIOVASCULAR RISKS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The main aim of this research is to analyze how IoT devices can help in the assessment of cardiovascular risks. This study delves into the composition and use of IoT devices outfitted with cutting-edge sensors and data analytical capabilities that continuously monitor essential physiological metrics linked to heart health viz. heart rate, blood pressure, and electrocardiogram-related figures. These contraptions enable seamless real-time data collection, transmission, and analysis thereby yielding valuable insights into an individual's heart condition [1]. The advent of the Internet of Things (IoT) has enabled healthcare professionals to monitor and evaluate medical conditions in real-time. This research delves into a practical experiment that focuses on the design and evaluation of an intelligent IoT instrument aimed at assessing short-term risks related to cardiovascular diseases. Heart diseases remain one of the primary causes of death globally, underscoring the significance of prompt risk analysis and intervention. The primary objective of this investigative inquiry lies in scrutinizing and dissecting the effectiveness of Internet of Things (IoT) devices concerning the appraisal of cardiac threats. The prevalence of cardiovascular ailments on a global scale underscores the need for innovative measures that efficiently keep tabs on hazards and devise ways to alleviate them[1]. Through thorough empirical analysis, this study sifts through accuracy, reliability, and practicality concerns surrounding IoT-oriented tools designed for measuring cardiac risks. Exhaustive trials involving diversified participants are carried out to accumulate data which is subsequently appraised employing statistical methodologies and machine learning algorithms. The research seeks to establish connections and trends within collected physiological data aiming at evaluating their relevance in predicting cardiovascular risks[2].